2013
DOI: 10.1002/pssa.201330308
|View full text |Cite
|
Sign up to set email alerts
|

Magnetron sputtering of epitaxial ZrB2 thin films on 4HSiC(0001) and Si(111)

Abstract: Epitaxial ZrB2 thin films were deposited at a temperature of 900 °C on 4H-SiC(0001) and Si (111) substrates by magnetron sputtering from a ZrB2 source at high rate ~80 nm/min. The films were analyzed by thin film X-ray diffraction including pole figure measurements and reciprocal space mapping as well as high resolution electron microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 16 publications
2
31
0
Order By: Relevance
“…When the deposition temperature is increased up to 550 °C the films exhibit a more random growth behavior with an increasing contribution from 101 ̅ 1-oriented grains [14]. Following those experiences, we demonstrated that it is possible to grow epitaxial films of ZrB2 on 4H-SiC(0001) substrates, with the epitaxial relationship of ZrB2(0001)║4H-SiC(0001) and ZrB2[1 1 ̅ 00]║4H-SiC[1 1 ̅ 00], in a laboratory scale ultra-high vacuum (UHV) system at 900 °C [15]. However, the growth behavior on 4H-SiC(0001) at temperatures between 550 °C and 900 °C remains to be investigated.…”
Section: Introductionmentioning
confidence: 66%
See 4 more Smart Citations
“…When the deposition temperature is increased up to 550 °C the films exhibit a more random growth behavior with an increasing contribution from 101 ̅ 1-oriented grains [14]. Following those experiences, we demonstrated that it is possible to grow epitaxial films of ZrB2 on 4H-SiC(0001) substrates, with the epitaxial relationship of ZrB2(0001)║4H-SiC(0001) and ZrB2[1 1 ̅ 00]║4H-SiC[1 1 ̅ 00], in a laboratory scale ultra-high vacuum (UHV) system at 900 °C [15]. However, the growth behavior on 4H-SiC(0001) at temperatures between 550 °C and 900 °C remains to be investigated.…”
Section: Introductionmentioning
confidence: 66%
“…The ZrB2 thin film growth was conducted in an UHV system with the same set-up and conditions as described elsewhere [15]. The substrates were outgassed in the growth chamber at 900 °C for 1 h. The temperature was then changed to a deposition temperature of either 500 °C, 600 °C, 700 °C, 820 °C or left at 900 °C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations